Susceptibility of Florida Mosquitoes to Infection with Chikungunya Virus - Reiskind, Michael H. (2008)
Chikungunya virus (CHIKV) has caused recent, large epidemics on islands in the Indian Ocean, raising the possibility of more widespread CHIKV epidemics. Historically, CHIKV has been vectored by Aedes aegypti, but these outbreaks likely also involved Ae. albopictus. To examine the potential for an outbreak of CHIKV in Florida, we determined the susceptibility to CHIKV of F(1) Ae. aegypti and Ae. albopictus from Florida. In addition, we also evaluated two well-characterized laboratory strains (Rockefeller and Lake Charles) of these species. We determined infection and dissemination rates as well as total body titer of mosquitoes 7 days post-exposure (pe) (Ae. albopictus) and 3, 7, and 10 days pe (Ae. aegypti). All mosquito strains were susceptible to both infection and dissemination, with some variation between strains. Our results suggest Florida would be vulnerable to transmission of CHIKV in urban and rural areas where the two vector species occur.